2022
DOI: 10.1109/jbhi.2022.3219123
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Multi-Phase CT Synthesis and Classification Framework for Kidney Cancer Diagnosis With Incomplete Data

Abstract: Multi-phase CT is widely adopted for the diagnosis of kidney cancer due to the complementary information among phases. However, the complete set of multi-phase CT is often not available in practical clinical applications. In recent years, there have been some studies to generate the missing modality image from the available data. Nevertheless, the generated images are not guaranteed to be effective for the diagnosis task. In this paper, we propose a unified framework for kidney cancer diagnosis with incomplete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…In Table 2, we compare the performance on the cGAN and PIX2PIX algorithms 8/19 implemented in our study with the performance of the two top-performing algorithms reported in a recent CECT renal image imputation study [32]. These algorithms are 1.…”
Section: Image Imputation Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Table 2, we compare the performance on the cGAN and PIX2PIX algorithms 8/19 implemented in our study with the performance of the two top-performing algorithms reported in a recent CECT renal image imputation study [32]. These algorithms are 1.…”
Section: Image Imputation Resultsmentioning
confidence: 99%
“…These algorithms are 1. DiagnosisGAN [32], which is a generative adversarial algorithm like the cGAN. However unlike the cGAN approach, it does not provide any information regarding the confidence in the imputation and further it requires segmented tumor images to improve its performance.…”
Section: Image Imputation Resultsmentioning
confidence: 99%
See 3 more Smart Citations